The developments of patrimony and the growth of tourism: conflicts surrounding the growth in the Quebrada de Humahuaca - Salleras, Lucila (Universidad Nacional del Litoral, 2020)
This article examines the conflicts that arise from the relationship between heritageand tourism development in the Quebrada de Humahuaca (Jujuy, Argentina), from itsinscription as world heritage for the Organization of United Nations for Education, Scienceand Culture (UNESCO) in 2003, under the category of cultural landscape.We analyzed the speeches that justified the inscription of the Quebrada to the World HeritageListand the process of patrimonial and tourist valorization. We work with the category ofdevelopment, taking into account its link with heritage. And finally, we analyse the tensionand demands arising from the uses of heritage and territory as an economic resourse for thedevelopment in the region.The doctoral investigation that sustains this article was carried out from a perspective socioanthropological and we used different methodological strategies for the collection, constructionand analysis of information from both primary and secondary sources.